Risk Assessment on Hull Painting Process at Shipyard - Wulandari, K N; Tualeka, A R; Widajati, N; Fitri, N (KnE Life Sciences, 2018)
The objective of this study was to conduct risk assessment on hull painting process and give the high-risk control recommendation at PT. X Surabaya. Methods of this study was a descriptive research with three steps of analysis. The first step was to identify all the potential hazards on hull painting process through observation and interview. The next step was to specify the likelihood and the consequence from each risk. And, the final step of analysis was to determine the risk value and its ranks. The highest risk got the priority of the recommendation. The results obtained showed that high risk can occur, among others, if hit by forklift, the fall of the machine being transported by a crane, a strung ladder, a fire and explosion, a fall from a height, and a hearing loss. Recommendations for high-risk hazard control include the formulation of policies or regulations, installation of signs that support policy, socialization of risk control policies, establishment of emergency response teams and first-aid teams, and socialization, monitoring, use and maintenance of personal protective equipment. The conclusion of this study was that the hull painting process had 22 hazard risks that consist of 6 high risks, 12 moderate risks and 4 acceptable risks. The high-risk control recommendation includes engineering control, administrative and the usage of personal protection equipment. Keywords: risk assessment, hull painting process, high-risk control recommendation